Mesenchymal Stem Cell Therapy on Tendon/Ligament Healing - Chamberlain, Connie S. (J Cytokine Biol, 2017)
A normal healing response after ligament and tendon rupture results in scar formation and an inferior tissue that fails to emulate its original structure, composition, and function. More regenerative healing (closer to the original) can be obtained through early suppression of inflammatory cells and associated cytokines. Examination of the immune mediated response of mesenchymal stem/stromal cells (MSCs) during healing indicates that MSCs reprogram macrophages from a pro-inflammatory M1 phenotype to an anti-inflammatory M2 phenotype. Based on these studies our objective was to treat ligament and tendon injuries with MSCs in order to modulate their inflammatory response. Our initial studies using allogeneic cells demonstrated an in vivo dose dependency of MSCs on ligament healing. Medial collateral ligaments (MCLs) treated with 1 × 10(6) (low dose) MSCs exhibited less inflammation and a reduced number of M1 macrophages compared to ligaments treated with 4 × 10(6) (high dose) MSCs. Strength of ligament was also improved with the low dose treatment. We then examined the in vivo effects of MSCs that had been preconditioned to be more anti-inflammatory. Treatment with these preconditioned MSCs was compared with normally processed (unconditioned) MSCs using the rat Achilles tendon and MCL healing models. Pre-conditioned MSCs significantly reduced inflammation by increasing the M2 macrophages and decreasing the M1 macrophages. Most importantly, treatment with pre-conditioned MSCs improved tissue strength to levels comparable to intact tissue. Overall, pre-conditioned MSC-treatment out-performed unconditioned MSCs to improve ligament and tendon healing by stimulating a more robust, paracrine-mediated immunosuppressive response.